Child Penalties and the Gender Gap in Home Production and the Labor Market - Pim Koopmans; Max van Lent; Jim Been (Institute of Labor Economics (IZA), 2024)
The consequence of the arrival of children for the gender wage gap - known as the child penalty - is substantial and has been documented for many countries. Little is still known about the impact of having children beyond paid work in the labor market, such as home production. In this paper we estimate - deploying an event study with Dutch survey data - the child penalty in both home production and the labor market. In line with the literature we find no labor market effects for men. For women we find a strong reduction in work hours and lower wages. However, we find an increase in home production for women roughly similar to the decline in paid work. Consequently, time allocated to the labor market plus home production is roughly equal across gender before and after the arrival of children. This result rejects the hypothesis that women substitute paid work for leisure after the arrival of children.
Keywords: C33; D12; D13; J16; J22; 330; gender gaps; child penalty; intra-household allocation; event study; home production